IMPROVED SLEEP QUALITY AND DECREASED INSOMNIA RATES AFTER YOGA THERAPY: LITERATURE REVIEW - Ningsih, Arum Dwi; Pratiwi, Rizky Meuthia (INTERNATIONAL JOURNAL OF NURSING AND MIDWIFERY SCIENCE (IJNMS), 2024)
Sleep quality is a problem that is often experienced by the elderly. In the elderly phase, humans will experience a decrease in organ function and this has an impact on meeting the needs of rest and sleep. Sleep quality in the elderly has decreased, this can be seen in sleep duration, sleep latency, and subjective aspects such as night sleep and rest. The purpose of this study was to conduct an analysis of Yoga Therapy on Sleep Quality Improvement and Insomnia in the Elderly. The literature study in this article is a literature review. The effect of the effectiveness of Yoga therapy on improving sleep quality and insomnia in the elderly will be reviewed, including how to sample and the variables measured. Database search and article screening are carried out independently by reviewers by following the requirements in meeting inclusion criteria. Based on the results of the Review of 16 research journals, 16 journals have quasy experiment, Pre-experimental studies and randomized control and trial research methods. A total of 16 journals show that Yoga Intervention can improve the quality of sleep in the elderly and help reduce insomnia symptoms in the elderly.